Bactericidal process and practicability for environmental water sterilization by solar-light-driven Bi2WO6-based photocatalyst. (June 2022) - Ming, Jie; Liu, Na; Ma, Qiansu; Sharma, Aditya; Sun, Xiang; Kawazoe, Naoki; Chen, Guoping; Yang, Yingnan
Abstract: Pathogenic microorganism has always been a major threat to human health, which results in infectious diseases and even massive death. In the present study, the solar-light-driven photocatalyst Ag/Ag2 O/BiPO4 /Bi2 WO6 was firstly used for water disinfection. The results showed the Ag/Ag2 O/BiPO4 /Bi2 WO6 composite completely inactivated 7.40 log10  cfu/mL Escherichia coli within only 20 min under light irradiation. The inactivation mechanism was systematically investigated from the antioxidant enzymes, cell membrane, intracellular components and active species involved in the disinfection process. At the early stage of disinfection, the antioxidant system was initiated and increased enzyme activities to fight oxidative attack. Unfortunately, with accumulation of oxidative damage, the activities of antioxidant enzymes were suppressed, leading to deterioration of defense system. After destruction of defense system, cell membrane was destroyed gradually, monitored by K + leakage and microscopic images. Furthermore, severe destruction of cell membrane led to leakage of nucleic acid and proteins, suggesting the irreversible death of bacteria. The photogenerated active species including superoxide radicals and holes played major roles in bactericidal process. In addition, the composite exhibited high adaptability for water disinfection at a wide range of environmental factors including light intensity, temperature, pH and humic acid. The slight release of Ag + (<0.1 mg/L) and high stability of photocatalysts during successive disinfection experiments further implied its great potential for application. This work introduced an efficient solar-light-driven photocatalyst Ag/Ag2 O/BiPO4 /Bi2 WO6, which exhibited a promising prospect for practical application, in hope of providing more useful information for water disinfection. Graphical abstract: Unlabelled Image Highlights: Solar-light-driven Ag/Ag2 O/BiPO4 /Bi2 WO6 was firstly used for water disinfection. Bactericidal process combined with disinfection mechanism was systematically clarified. The photocatalyst exhibited excellent antibacterial activity with high safety and stability. The photocatalyst showed high adaptability in wide environmental factors. The novel composite possesses great potential for real water disinfection.